Digital Newspaper as An Alternative Solution to Maintain The Existence ff Print Media in PT Okt - Oktoviani, Maria Bernadetta Erika; Kurniasari, Florentina; Juliadi, Rismi (Conference Series, 2021)
PT OKT Print Media needs to do a dual transformation to reposition its business to survive in the industry, create a new form of media to reach long distribution distances and to reach market segments that were previously unreachable, as well as to gain new business benefits. The transformation into a Digital Newspaper is carried out by changing the manual marketing process into digital marketing, and creating new html-based media with distribution via data-based and whatsapp. By enriching photos and videos as product development and segmentation that were previously unaffordable, and overcoming the problem of unreachable distribution.There are not many other studies that discuss the digital transformation from physical newspapers to digital newspapers using the Digital Maturity Model (DMM) from TM Forum. Using a 5-dimensional DMM-based questionnaire and 100 samples of customer and employee research, the maturity level of the company's current digital transformation process can be mapped, for the results to be validated by the Commercial Director as the basis for compiling a road map for further improvement. The findings of this study recommend that PT OKT Digital Newspaper uses a digital transformation strategy in the form of Digital Newspaper in order to survive for the purpose of maintaining its existence and adapting to its business environment.